Industrial Relations in Schools - Ironside, Mike (Taylor & Francis, 1995)
The subject of industrial relations is intimately connected with the nature of schooling - in particular, the teacher trade unions have played and will continue to play a crucial role in shaping the school system - yet this subject has been virtually neglected in educational literature. Mike Ironside and Roger Seifert's book redresses this balance and unravels the complex issues surrounding the employment and management of teachers. Recent changes in education have had massive implications for the way in which our education system is organised. In the light of recent events, this book questions who controls or ought to control schools, focusing on the government, Department of Education, LEA's, head teachers, school governors, parents and teaching unions. The authors argue that in order for schools to continue to function, industrial relations must be given priority, including the development of a proper framework for negotiation and the resolution of conflicts.